2020
DOI: 10.1155/2020/8798974
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effects of Transcutaneous Electrical Acustimulation at Neiguan (PC6) and Zusanli (ST36) Acupoints Combined with Adaptive Biofeedback Training on Functional Outlet Obstruction Constipation

Abstract: Background. Stimulant laxatives are still considered the most common treatment for functional outlet obstruction constipation (FOOC). However, the effectiveness of laxatives is unsatisfactory, and the long-term use of laxatives may cause certain adverse events. With this in mind, it is, however, paramount that novel complementary treatment(s) and/or other forms of alternative medicine are adequately investigated. Aims. The study aims to explore the effects and potential mechanism(s) of transcutaneous electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Of note, Liu et al (2018) documented that an escalation in sympathetic nerve activity is associated with constipation. Meanwhile, our previous study showed that the imbalance between sympathetic and parasympathetic nerves plays a vital role in constipation symptoms ( Liu et al, 2020 ). Notably, the current study showed that sleep disorders will influence the balance between parasympathetic and sympathetic nerves thus remarkably increasing sympathetic activities, which is similar outcomes to previous research ( Carter et al, 2018 ; Wang S. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, Liu et al (2018) documented that an escalation in sympathetic nerve activity is associated with constipation. Meanwhile, our previous study showed that the imbalance between sympathetic and parasympathetic nerves plays a vital role in constipation symptoms ( Liu et al, 2020 ). Notably, the current study showed that sleep disorders will influence the balance between parasympathetic and sympathetic nerves thus remarkably increasing sympathetic activities, which is similar outcomes to previous research ( Carter et al, 2018 ; Wang S. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…All FC patients underwent HRAM (MedKinetic, Ningbo, China), and the process of HRAM was described in our previous research ( Liu et al, 2020 ). Each patient received 1–2 doses of glycerin enema for bowel preparation 30–60 min prior to the HRAM test.…”
Section: Methodsmentioning
confidence: 99%
“…HRAM and balloon expulsion test (BET) are recommended as the first modalities to evaluate these patients. The principal objective of performing physiologic tests for constipated patients is to identify those with DD, as these patients would respond well to biofeedback therapy [ 13 , 28 ]. In short, the results of anorectal physiologic tests were directly associated with subsequent treatment choices for constipated patients.…”
Section: Discussionmentioning
confidence: 99%
“…All participants underwent a HRAM test (Med Kinetic, Ningbo, China), and the results were recorded by a single experienced investigator (J L), as described in our previous research [ 13 ]. An anorectal catheter was inserted in each patient's rectum, and anal resting pressure (ARP) was measured using a water-perfused anorectal manometric catheter equipped with eight pressure sensors at 1 cm interval.…”
Section: Diagnostic Studymentioning
confidence: 99%
“… Wu et al (2020) designed a cross-over study to compare the effectiveness of TEA at ST36 and TEA at PTN in treating functional constipation and found that TEA was more potent at ST36 than at PTN in improving constipation and the constipation-related symptoms. Liu et al (2020) reported the ameliorating effects of TEA at the Neiguan (PC6) and ST36 acupoints combined with adaptive biofeedback training in patients with functional outlet obstruction constipation. However, these studies were all conducted in a single center and lacked comprehensive analysis of constipation symptoms and rectal sensation.…”
Section: Introductionmentioning
confidence: 99%